Effects of low-versus high-volume high-intensity interval training on glycemic control and quality of life in obese women with type 2 diabetes: A randomized controlled trial - Ahmad Mahdi Ahmad; Asmaa Mohamed Mahmoud; Zahra Hassan Serry; Mohamed Mady Mohamed; Heba Ali Abd Elghaffar (Journal of Exercise Science & Fitness, 2023)
Background/objective: Comparison between different training volumes of high-intensity interval training (HIIT) is understudied in type 2 diabetes. This study aimed to compare the effects of low- and high-volume HIIT on glycemic control, blood lipids, blood pressure, anthropometric adiposity measures, cardiorespiratory fitness, and health-related quality of life (HRQoL) in women with type 2 diabetes. Methods: Seventy-two obese women with type 2 diabetes aged 36–55 were randomly assigned to a low-volume HIIT group (i.e., 2 × 4-min high-intensity treadmill exercise at 85%–90% of peak heart rate, with a 3-min active recovery interval in between), a high-volume HIIT group (i.e., 4 × 4-min high-intensity treadmill exercise at 85%–90% of peak heart rate, with three 3-min active recovery intervals in between), and a non-exercising control group. Patients in HIIT groups exercised three days a week for 12 weeks. All patients received oral hypoglycemic medications with no calorie restrictions. The outcome measures were glycosylated hemoglobin (HbA1c), fasting blood glucose (FBG), 2-hour postprandial blood glucose (2-hr PPBG), total cholesterol (TC), triglyceride (TG), low-density lipoprotein (LDL), high-density lipoprotein (HDL), systolic blood pressure (SBP), diastolic blood pressure (DBP), body mass index (BMI), waist circumference (WC), waist-to-hip ratio, time to maximal exhaustion determined from a maximal treadmill exercise test (i.e., a measure of cardiorespiratory fitness), and HRQoL assessed by the 12-item Short Form (SF-12) Health Survey. Results: The low- and high-volume HIIT groups showed significant improvements in all outcome measures compared to the baseline and the non-exercising group (P < 0.05), except for DBP in the low-volume HIIT group (p > 0.05). Also, both low- and high-volume HIIT groups showed similar improvements in TC, HDL, SBP, DBP, BMI, WC, waist-to-hip ratio, and the SF-12 scores, with no significant between-groups difference (p > 0.05). The high-volume HIIT group, however, showed more significant improvements in HbA1c, FBG, 2-hr PPBG, TG, LDL, and treadmill time to maximal exhaustion than the low-volume HIIT group (p < 0.05). The non-exercising group showed non-significant changes in all outcome measures (p > 0.05). Conclusion: Low-volume HIIT could be equally effective as high-volume HIIT for improving TC, HDL, blood pressure, anthropometric adiposity measures, and HRQoL in obese women with type 2 diabetes. Nevertheless, high-volume HIIT could have a greater impact on glycemic control, TG, LDL, and cardiorespiratory fitness in these patients. Trial registration: ClinicalTrials.gov, NCT05110404.